2017
DOI: 10.1631/jzus.b1600208
|View full text |Cite
|
Sign up to set email alerts
|

Porcine circovirus type 2 capsid protein induces unfolded protein response with subsequent activation of apoptosis

Abstract: Porcine circovirus type 2 (PCV2) has recently been reported to elicit the unfolded protein response (UPR) via activation of the PERK/eIF2α (RNA-activated protein kinase-like endoplasmic reticulum (ER) kinase/eukaryotic initiation factor 2α) pathway. This study attempted to examine which viral protein might be involved in inducing UPR and whether this cellular event would lead to apoptosis of the cells expressing the viral protein. By transient expression, we found that both replicase (Rep) and capsid (Cap) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…PCV2 infection induces ERS and activates the PERK/eIF2α pathway in UPR, and ERS may play a role in PCV2 infection as part of autophagy and apoptosis , as well as the PERK pathway also regulates autophagosome formation . The Rep and Cap proteins of PCV2 induced UPR by the phosphorylation of PERK with subsequent activation of the eIF2α-ATF4 pathway (Zhou et al, 2017). In the present study, we showed that ORF5 protein activates eIF2α-ATF4 expression by phosphorylating PERK which is consistent with the above studies.…”
Section: Discussionsupporting
confidence: 92%
“…PCV2 infection induces ERS and activates the PERK/eIF2α pathway in UPR, and ERS may play a role in PCV2 infection as part of autophagy and apoptosis , as well as the PERK pathway also regulates autophagosome formation . The Rep and Cap proteins of PCV2 induced UPR by the phosphorylation of PERK with subsequent activation of the eIF2α-ATF4 pathway (Zhou et al, 2017). In the present study, we showed that ORF5 protein activates eIF2α-ATF4 expression by phosphorylating PERK which is consistent with the above studies.…”
Section: Discussionsupporting
confidence: 92%
“…These findings, together with earlier observations of immune stimulation of viral replication (3), suggest that stress factors that perturb cellular responses are most likely in favor of PCV2 replication. Previous work in our laboratory showed that PCV2 infection initiated autophagy via activation of CaMKK␤ by increased cytosolic Ca 2ϩ levels (27) and that PCV2 utilizes its Cap protein to induce ER stress by PERK activation, which eventually leads to an apoptotic response (28). Because the ER is the major reservoir of Ca 2ϩ , we postulate that PCV2-induced ER stress leads to a cellular Ca 2ϩ imbalance that affects important cellular responses, including apoptosis.…”
Section: Discussionmentioning
confidence: 77%
“…The cell viability of PK-15 and PAM cells treated with the chemicals was assayed with cell counting kit 8 (Dojindo), following the manufacturer's instruction. Previous studies showed that treatment with these chemicals did not have significant effects on the viability of PK-15 and PAM cells (15,27,28).…”
Section: Discussionmentioning
confidence: 94%
“…Likewise, PCV2 ORF4 protein was also reported to be associated with apoptosis by inducing the activities of casp-3 and casp-8 (19,45). In addition, the PCV2 ORF3 protein was observed to activate casp-9 and casp-8 for induction of apoptosis (44), and PCV2 Cap was considered to promote apoptosis via decreasing antiapoptotic B-cell lymphoma-2, involved in regulation of mitochondrial apoptosis (65,66). Lymphopenia has been reported as a main histopathological characteristic in the lymph nodes of PCV2-infected organisms (36,(67)(68)(69).…”
Section: Discussionmentioning
confidence: 99%